2013
DOI: 10.3892/ijo.2013.2175
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-loaded nanoparticles enhance apoptotic cell death of U2OS human osteosarcoma cells through the Akt-Bad signaling pathway

Abstract: Curcumin has potential anticancer activity and has been shown to be involved in several signaling pathways including differentiation and apoptosis. Our previous study showed that water-soluble PLGA curcumin nanoparticles (Cur-NPs) triggered apoptotic cell death through regulation of the function of MDR1 and the production of reactive oxygen species (ROS) in cisplatin-resistant human oral cancer CAR cells. In this study, we investigated the anti-proliferative effects of Cur-NPs on human osteosarcoma U2OS cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(33 citation statements)
references
References 67 publications
(63 reference statements)
0
33
0
Order By: Relevance
“…In addition to influencing the expressions of apoptosis and anti-apoptosis genes, Akt can also promote cell survival through the direct phosphorylation of protein BAD [25,26]. AKT phosphorylates and inhibits BAD, thus preventing its binding and inhibition of Bcl-2 and Bcl-xl [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to influencing the expressions of apoptosis and anti-apoptosis genes, Akt can also promote cell survival through the direct phosphorylation of protein BAD [25,26]. AKT phosphorylates and inhibits BAD, thus preventing its binding and inhibition of Bcl-2 and Bcl-xl [27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Since the majority of anticancer strategies initiate apoptosis through caspase 9 activation, the modulation of caspase 9 expression may be exploited by designing new ways to control apoptosis in malignant tumors, including GBM [39]. There are a lot of publications about the interactions between different types of nanoparticles and tumor cells which have shown that titanium dioxide nanoparticles as well as curcumin-loaded nanoparticles cause intrinsic-mediated apoptosis in human cells and that caspase 9 plays a critical role in this process [40,41]. However, none of these publications focused on the activation of caspase 9 in GBM.…”
Section: Discussionmentioning
confidence: 99%
“…The most of the proposed delivery nano-systems show mechanisms of action mirror that of free curcumin, allowing an effective passive targeting on different cancer cells, including cervical (Das et al, 2010), oral (Chang et al, 2013a), prostate (Mukerjee & Vishwanatha, 2009;Sanoj Rejinold et al, 2011), breast (Sanoj Rejinold et al, 2011 cancers, osteosarcoma (Peng et al, 2014), melanoma (Mangalathillam et al, 2012), and medulloblastoma (Altunbas et al, 2011) by controlling the CUR release over time. Furthermore, in vivo studies proved that nanoparticles prepared by free radical polymerization of N-isopropylacrylamide (NIPAAm), N-vinyl-2-pyrrolidone (VP), and poly(ethylene glycol) acrylate (PEG-mA), proposed for the treatment of pancreatic cancer, show negligible toxicity in mouse model (Bisht et al, 2007), while the emulsion polymerization of butyl-cyanoacrylate in the presence of CT allows the obtainment of a CUR delivery vehicles suitable for the treatment of hepatic cancer with favorable pharmacokinetic profiles (Duan et al, 2010).…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%